(untitled) (Journal of Pharmaceutical Negative Results, 2023)
In this work, we study the first level of poultry network which contained several farms (poultry houses) dedicated to broiler breeding. For breeding the necessary conditions must be respected, using good feeding, veterinary care, adequate ventilation and ambient heating which may be gas or electric etc. The problem of this network is the installation of the heating system, more precisely the main problem is to choose between a gas or an electric heater. Knowing that the gas heating has a low cost but a rather high emission of carbon dioxide which is harmful for the liveliness of chickens and the environment in general, on the other hand, the electric heating is very recommendable because of the low rate of resignation of CO2, that said its high cost hinders considerably the breeders. To find an intermediate solution that minimizes the different costs while respecting the environmental aspect we propose in this work a multi-objective mathematical modelling that minimizes the heating costs and minimizes the carbon dioxide emissions. Both objectives are optimized independently, then after LP-metric aggregation is used to combine them to find the optimal solution.